Variables Analysis of Tourism Apps Development in Influencing Tourist Travel Experience - Qistina Donna Lee, Abdullah; Aimuni Athirah, Latif (Blue Eyes Intelligence Engineering andSciences Publication, 2020)
Dumping of apps that emphasized on how to develop tourism industry and help travel organization to promoting their business. However, every app has own advantages and disadvantages. Producing an apps need a properly research about needs and demands of tourist or traveller itself. The tourism apps have its own influence towards tourists when it’s come to their satisfaction of travelling.Producing of tourism apps can be expansion if the producer increases the requirements, by doing a research of tourist’s needs and demand.Every tourist has their own needs and demands that are influenced by their preference, identity and family background. These factors are developed from many criteria, such as their culture which influence their identity, and their power of buying which influences their taste and preferences. Tourism industry is a wide field, before certain products are produced and certain services are offered, the producers need to analyse their target market.Thus, the success of a tourism App depends on how well and deep the producer has managed to explore and study about the target users. Research that linked between product and user needs on tourism apps area big deal to explore.Successful of apps depends on how producer of tourism apps study about the users. The finding of paper is variables analysis of tourism apps that can be used to developing new prototype of tourism apps based on tourist needs.This paper will introduce the best variables that have been analysing to be interesting features that can be including in tourism apps.